Social to Moderate Alcohol Consumption Provides a Protective Effect for Functional Outcomes After Fixation of Orthopaedic Fractures. Issue 6 (June 2017) - Saleh, Hesham; Driesman, Adam; Fisher, Nina; Leucht, Philipp; Konda, Sanjit; Egol, Kenneth
Abstract : Objectives: To identify the association between social and moderate alcohol consumption and functional outcomes after surgical management of orthopaedic fractures. Design: Prospective cohort study. Setting: Level 1 trauma center. Patients/Participants: Seven hundred eighty-four patients who were operatively treated for an isolated orthopaedic fracture were prospectively followed. Patients were categorized into groups according to self-reported drinking frequencies based on NIAAA guidelines. Main Outcome Measurements: SMFA scores at baseline, 3, 6, and 12 months postoperatively; postoperative complications; and subsequent operations. Results: There were 367 (46.8%) abstinent, 327 (41.7%) social, 52 (6.6%) moderate, and 38 (4.8%) heavy drinkers. Mean SMFA scores of social and moderate drinkers were significantly lower than those of abstinent patients at 3-, 6-, and 12-month follow-ups, denoting better functional outcomes (social: 24.3 vs. 30.5, P = 0.001; 14.8 vs. 21.5, P < 0.005; and 10.1 vs. 18.8, P < 0.005); (moderate: 18.3 vs. 30.5, P = 0.001; 9.7 vs. 21.5, P = 0.001; and 5.4 vs. 18.8, P < 0.005). Multiple linear regression revealed that social drinking and baseline SMFA scores were the only statistically significant independent predictors of lower SMFA scores at 12 months after surgery. Conclusions: Social to moderate drinking may have a protective effect on functional outcomes at 3, 6, and 12 months after surgery. Social drinking may also have a protective effect on postoperative complications and reoperation rates. Further studies should be performed to fully appreciate the clinical effect of social and moderate drinking after operative treatment of orthopaedic fractures. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.